Roles of ion irradiation and thermal annealing in inducing crystallization in metallic glass. (November 2019) - Liang, Y.X.; Du, J.L.; Xu, C.; Wang, P.P.; Hu, Z.Y.; Qiu, Y.H.; Wang, P.; Fu, E.G.
Abstract: We studied the crystallization behavior of metallic glass Ni50 Nb10 Zr15 Ti15 Pt7.5 Cu2.5 under different ion irradiation and thermal annealing conditions. The results show that although the room temperature ion irradiation would not introduce observable structural defects in metallic glass, the excess free volume induced by ion irradiation would promote the formation of nanocrystals under thermal annealing. Meanwhile, the interstitial atoms induced by high temperature ion irradiation may act as an important role in the enhancement of atomic diffusivity and nanocrystals growth process. Our study shows that the combination of ion irradiation and thermal annealing may help to achieve controllable structural modification of metallic glass. Highlights: Excessive free volume promotes the growth of nanocrystals in metallic glass. Under high temperature ion irradiation, interstitial type atoms may contribute to the formation of nanocrystals. The combination of ion irradiation and thermal treatment can achieve optimal structural engineering for metallic glass.